2005
DOI: 10.1007/s00216-004-3046-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of near-infrared reflectance spectroscopy in predicting nitrogen, phosphorus and calcium contents in heterogeneous woody plant species

Abstract: Near-infrared reflectance spectroscopy was applied to determine nitrogen (N), phosphorus (P) and calcium (Ca) content in leaf samples of 18 woody species. A total of 183 samples from mountain, riparian and dry areas from the Central-Western Iberian Peninsula were collected for this purpose. The wide intervals of variation observed in nutrient concentrations (6.6-45.0 g kg(-1) for N, 0.24-2.97 g kg(-1) for P, and 1.00-20.06 g kg(-1) for Ca) were due to the great heterogeneity of the samples. To develop calibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
53
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 26 publications
13
53
1
3
Order By: Relevance
“…Derivative models improved predictions and parsimony across all nutrients. This result agrees with a similar study by Petisco et al (2005) that obtained better results using first and second derivative transformations for N, P, and Ca than the logarithm transformation. Furthermore, Karnieli, Karnieli, and Bonfil (2007) found greater success with derivatives and wavelength selection than the full spectrum of reflectance measurements for N predictions.…”
Section: Regional Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…Derivative models improved predictions and parsimony across all nutrients. This result agrees with a similar study by Petisco et al (2005) that obtained better results using first and second derivative transformations for N, P, and Ca than the logarithm transformation. Furthermore, Karnieli, Karnieli, and Bonfil (2007) found greater success with derivatives and wavelength selection than the full spectrum of reflectance measurements for N predictions.…”
Section: Regional Analysissupporting
confidence: 93%
“…Asner et al (2011) used PLSR on imaging spectroscopy data to predict macronutrients in tropical forest canopies consisting of several thousand plant species; they obtained R 2 values for N, P, K, Ca, and Mg of 0.77, 0.63, 0.51, 0.65, and 0.57, respectively. Similarly, Petisco et al (2005) found much higher R 2 values for N, P, and Ca (R 2 = 0.99, 0.94, and 0.95) across 18 different woody plant species in the Iberian Peninsula. The absorbance transformations, major indices, and subsets of selected wavelengths did not considerably improve the explanatory power of the models.…”
Section: Regional Analysismentioning
confidence: 82%
“…The number of PLS components deemed optimal in the final variable selection with respect to RMSE CV was one, resulting in a model of low complexity. This identified wavelength range for determining phosphorus agrees with wavelength regions which have previously been reported in studies of phosphorus content in dried woody plant species 20 and in soil. 21 The latter study in soil phosphorus concentration also found large regression coefficient values at other wavelengths, including the visible region.…”
Section: Wavelength Selectionsupporting
confidence: 89%
“…It is well known that total nitrogen (N), inorganic ash (ash), crude fibre (CF), ether extract (EE) and nitrogen free extracts (NFE) can be determined with NIRS (e.g. [32,45] as well as mineral compositions [38,33,16]. However, most studies concentrate on pure sample sets of wheat [25], maize silage [11,23], herbages, grass silages [30,2], legumes [19,9], rice [48] sunflower [26] or hemp [44].…”
Section: Focus Of This Studymentioning
confidence: 98%